Merkel Cell Carcinoma: An Immunotherapy Fairy-Tale? - Tanda, Enrica Teresa; d’Amato, Agostina Lagodin; Rossi, Giovanni; Croce, Elena; Boutros, Andrea; Cecchi, Federica; Spagnolo, Francesco; Queirolo, Paola (Frontiers in Oncology, 2021)
Merkel Cell Carcinoma (MCC) is a rare, highly aggressive, neuroendocrine cutaneous tumor. The incidence of MCC is growing worldwide and the disease-related mortality is about three-fold higher than melanoma. Since a few years ago very little was known about this disease, and chemotherapy was the standard of care. Nowadays, new discoveries about the pathophysiology of this neoplasm and the introduction of immunotherapy allowed to completely rewrite the history of these patients. In this review, we provide a summary of the most important changes in the management of Merkel Cell Carcinoma, with a focus on immunotherapy, and a landscape of future treatment strategies.